2016
DOI: 10.1002/ejic.201600420
|View full text |Cite
|
Sign up to set email alerts
|

Ligands with Two Different Binding Sites and O2 Reactivity of their Copper(I) Complexes

Abstract: The synthesis of two new unsymmetric dinucleating ligand systems, L1, combining a bidentate binding site with a tridentate binding site linked through a dibenzofuran spacer, and L2, with two tridentate binding sites bridged by an ethylene spacer, is reported. The ligands L1 and L2 were used for the preparation of the dicopper(I) complexes [Cu2(L1)(NCCH3)3](X)2, {[Cu2(L1)Cl2]}n and [Cu2(L2)(NCCH3)2](Y)2 (X = PF6, BF4, OTf; Y = ClO4, PF6, BF4), in which the two respective copper ions possess two different coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…However, these hybrid dicopper(I) complexes show different reactivities toward O 2 . 273 To develop copper−dioxygen complexes as synthetically useful oxidants, a suitable ligand design that can generate stable yet reactive metal complexes is essential. Toward this end, the coordination chemistry of bidentate N-donor ligands has attracted increasing attention.…”
Section: Dicopper Modelsmentioning
confidence: 99%
“…However, these hybrid dicopper(I) complexes show different reactivities toward O 2 . 273 To develop copper−dioxygen complexes as synthetically useful oxidants, a suitable ligand design that can generate stable yet reactive metal complexes is essential. Toward this end, the coordination chemistry of bidentate N-donor ligands has attracted increasing attention.…”
Section: Dicopper Modelsmentioning
confidence: 99%
“…The palette of functions that can be introduced at a xanthene backbone was continuously extended by various main group units like silylenes[1b] or bismuthanes; furthermore instead of the xanthene also dibenzofuran was used as a linker unit to vary the distance between the two functions. Sophisticated ways were found to also connect stepwise typical transition metal binding pockets as modules to such spacers (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…Resulting compounds proved capable of activating substrates like O 2 ,[1b], N 2 O, H 2 [1a], H 2 O,[1b] and CO 2 [1b].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of model complexes described in the literature display a symmetrical binuclear copper site, and the use of unsymmetrical dicopper model complexes in terms of structure and reactivity has been underexplored compared to the symmetrical ones. Nevertheless, some models of dinuclear copper oxidases have been designed with unsymmetrical cores. For instance, Itoh et al reported two different pentapyridine dicopper­(I) complexes that both yield μ-η 1 :η 1 peroxo dicopper complexes in the presence of dioxygen. , Interestingly, it was found that one of the peroxo complexes displays unusual both electrophilic and nucleophilic properties associated with the specific design of the ligand. In another example, an unsymmetrical ligand with different coordination cores separated by a phenyl ( m -xylyl) linker was reported.…”
Section: Introductionmentioning
confidence: 99%